Моделювання роботи локаційної системи в різноманітних умовах спостереження - Головатенко, С. В.; Стрілкова, Т. О. (ХНУРЕ, 2025)
This research is dedicated to the development of software for modeling the operation of a location system under various observation conditions. The research presents the advantages and disadvantages of radio and optical location tools. The main factors affecting optical location systems are discussed. The structure of the informational model for the process of registering optical radiation by optical location systems is presented. The issues of modeling optical processes are considered, and methods for generating data to simulate external and internal interference are outlined.
Keywords: спостереження; робота локаційної системи